2011
DOI: 10.1007/s12555-011-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical genetic algorithm based RBF neural networks and application for modelling of the automatic depth control electrohydraulic system

Abstract: The paper presents an approach to model nonlinear dynamic behaviors of the Automatic Depth Control Electrohydraulic System (ADCES) of a certain minesweeping weapon with Radial Basis Function (RBF) neural networks trained by hierarchical genetic algorithm. In the proposed hierarchical genetic algorithm, the control genes are used to determine the number of hidden units, and the parameter genes are used to identify center parameters of hidden units. In order to speed up convergence of the proposed algorithm, wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The hierarchical genetic algorithms (HGA) (Xing et al 2011; Barreto et al 2006) were put forward based on the hierarchy of biological chromosome which has two parts: controlling genes and parameter genes. The controlling genes which determine whether the parameter genes are activated, are expressed in binary form, in which “1” indicates that the underlayer genes are active, while “0” indicates that the underlayer genes are inactive.…”
Section: Hhga Optimizes Rbf Neural Networkmentioning
confidence: 99%
“…The hierarchical genetic algorithms (HGA) (Xing et al 2011; Barreto et al 2006) were put forward based on the hierarchy of biological chromosome which has two parts: controlling genes and parameter genes. The controlling genes which determine whether the parameter genes are activated, are expressed in binary form, in which “1” indicates that the underlayer genes are active, while “0” indicates that the underlayer genes are inactive.…”
Section: Hhga Optimizes Rbf Neural Networkmentioning
confidence: 99%
“…Moreover, genetic algorithm was adopted in the calculation and the calculation results were compared with the experimental data. The comparison results indicated that this method allowed satisfactory results [18]. Shi and Reitz studied NSGAII applications under different strategies and indicated that the NSGAII was superior to other commonly used algorithms for engine performance optimization [19,20].…”
Section: Introductionmentioning
confidence: 97%
“…The use of Neural Networks (NN) for identification of nonlinear models has already been explored [10][11][12]. Suthradar et al [13] demonstrates both identification and control of nonlinear dynamical systems using static and dynamic back-propagation methods.…”
Section: Introductionmentioning
confidence: 99%